Seasonal variation in physio-biochemical responses in osmanabadi goat kids: growth assessment by alkaline phosphatases as a biomarker - wankar, alok Khemraj; Kekan, Prakash Madhukarao; Daware, Sudhir Bapurao; Amrutkar, Suhas Ashokrao; Bhagat, Yogesh Deoram; Chobe, Poonam Hanumant; Pangaonkar, Laxmikant Ashokrao (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The present study was planned to assess the impact of different seasons and temperature humidity index (THI) on physiology, metabolism, and growth performance in osmanabadi kids. For the study, 06 kids (0-3 months) were reared under a semi-intensive system and exposed to three different seasons, viz., summer (April-May), monsoon (July-August) and winter (December-January). Physiological and meteorological variables were recorded at weekly intervals, while for biochemical estimations, blood was collected, at a 15-day interval. Body temperature and respiration rates were higher in summer and winter, while the heart rate was highest during summer (P
Keywords: Alkaline phosphatase; Growth biomarker; Osmanabadi goat kid; Temperature humidity index